Occupational Therapy Students’ Perceptions of OSCE: A Qualitative Descriptive Analysis - Nancy E. Krusen (Journal of Occupational Therapy Education, 2020)
Objective Structured Clinical Examinations (OSCE) are commonly used across health professions educational programs to evaluate student clinical competencies. OSCE are multiple, brief stations representing common practice scenarios. The purpose of the study was to evaluate student perceptions of OSCE. The researchers implemented 17 OSCE stations with 40 second year occupational therapy students to assess clinical competencies prior to fieldwork. Applying a qualitative descriptive methodologic approach, researchers analyzed station rating data, Qualtrics survey Likert-type items, and Qualtrics survey open-ended responses. Number of station rating responses varied widely, due to perceived time press. Station rating responses confirmed the more robust 80% response to Qualtrics survey. Analysis of Likert-type items revealed perceptions of OSCE as comprehensive, mixed eustress and distress, confirming of competence, and supportive of growth. Four dimensions of learning emerged from analysis of open-ended items: temporal, real world, bottlenecks to learning, and being open to the process. Findings affirmed student perceptions of OSCE to be valuable as summative and formative assessment of clinical competence. Existing literature supports three of the four dimensions of learning. The researchers advocate additional research to examine bottlenecks to learning, psychometrics of OSCE, the use of OSCE in program evaluation, and longitudinal study of student performance related to OSCE.